Protective effects of escin against indomethacin-induced gastric ulcer in mice. (20th October 2014) - Wang, Tian; Zhao, Shanshan; Wang, Yucun; Yang, Yujiao; Yao, Le; Chu, Liuxiang; Du, Hanhan; Fu, Fenghua
Abstract: Escin, a natural mixture of triterpenoid saponin isolated from the seed of the horse chestnut, is reported to have a potent antiulcer activity against ethanol-induced gastric mucosal lesions. This study investigated the possible mechanisms underlying the gastroprotective effect of escin against indomethacin-induced gastric ulcer in mice. Gastric ulceration was induced by a single intragastric administration of indomethacin (18 mg/kg). The mice underwent intragastric treatment with escin at doses of 0.45, 0.9 or 1.8 mg/kg. Gastric lesion was estimated morphometrically and histopathologically 6 h after the indomethacin administration. The antioxidative parameters in gastric mucosa were measured. Moreover, the activity of myeloperoxidase and the contents of TNF-α, P-selectin and VCAM-1 in gastric tissues were determined. The results showed that escin protected gastric tissues against indomethacin-induced gastropathy as demonstrated from a reduction in the ulcer index and an attenuation of histopathologic changes. Escin caused significant reductions of the contents of malondialdehyde, TNF-α, P-selectin, VCAM-1 and myeloperoxidase activity. The altered activities of superoxide dismutase, catalase and glutathione peroxidase in the stomach tissues were also ameliorated by escin treatment. The present study demonstrated that escin had a protective effect against indomethacin-induced gastric ulcer in mice, not only by virtue of its antioxidant potential, but also due to its anti-inflammatory effect.